Luther and Norwegian Nation-Building - Anders Aschim (Nordlit: Tidsskrift i litteratur og kultur, 2019)
In most Protestant countries, the Reformation was closely connected to the development of vernacular languages and literatures. In Norway under Danish rule, this was not the case. Only in the 19th century, during the nation-building period of independent Norway, a Norwegian ecclesiastical language was developed. Some authors claim that this completed the Reformation in Norway – a protracted Reformation indeed. Particularly important were the hymns of Magnus Brostrup Landstad and Elias Blix.